AARNet’s Cloudstor+ Cloud storage initiative: Cloud-based value-added services - Reid, Alex (Journal of Telecommunications and the Digital Economy, 2014)
This paper describes the rationale behind AARNet’s involvement in providing a range of value-added services over its Research and Education high-speed network. Special emphasis is given to services offered ‘in the Cloud’, and in particular concentrating on its latest service offering, Cloudstor+, which provides Cloud storage to researchers across Australia.